2005
DOI: 10.1002/syn.20122
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and serotonin release in dorsal striatum and nucleus accumbens is differentially modulated by morphine in DBA/2J and C57BL/6J mice

Abstract: Numerous studies have demonstrated that genetic factors significantly influence opioid ability to induce behavioral modification in mice. This differential sensitivity has been extensively studied, particularly in the DBA/2J and C57BL/6J strains. In the present study, using the "in vivo" microdialysis technique in these strains, we investigated the effect of morphine administration on the extracellular levels of dopamine (DA), serotonin (5-HT), and their metabolites in the nucleus accumbens and dorsal striatum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 48 publications
3
37
1
Order By: Relevance
“…Microdialysis and voltammetry measurements have shown that the extracellular DA concentration is lower in the NAc than in the dorsal striatum (Jones et al, 1995;Keck et al, 2002;Cragg, 2003;Melendez et al, 2003;Fadda et al, 2005). We found that lower basal DA release (i.e., DA release evoked by 1p) correlated with stronger facilitation of DA release in the NAc shell during phasic stimulation.…”
Section: Tonic and Phasic Dopamine Transmission In The Striatummentioning
confidence: 51%
“…Microdialysis and voltammetry measurements have shown that the extracellular DA concentration is lower in the NAc than in the dorsal striatum (Jones et al, 1995;Keck et al, 2002;Cragg, 2003;Melendez et al, 2003;Fadda et al, 2005). We found that lower basal DA release (i.e., DA release evoked by 1p) correlated with stronger facilitation of DA release in the NAc shell during phasic stimulation.…”
Section: Tonic and Phasic Dopamine Transmission In The Striatummentioning
confidence: 51%
“…In addition, administration of a dopamine D2 receptor antagonist, or combined D1-D2 receptor antagonism, attenuates the locomotor stimulant response to ethanol in FAST mice (Shen et al, 1995a). Similarly, morphine elicits increases in extracellular dopamine levels in the NAc (Fadda et al, 2005;Murphy et al, 2001) and dopamine depletion or D1 receptor antagonism diminishes the acute locomotor stimulant response to morphine in mice (Hnasko et al, 2005;Jeziorski & White, 1995). Therefore, ethanol-and morphineinduced locomotor stimulation in FAST mice may be occurring through a similar activation of mesolimbic dopamine systems.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was shown that fentanyl can engender some discriminative stimulus properties of cocaine (Colpaert et al, 1979) and amphetamine produces an increasing amount of fentanyl-appropriate responding when the training doses is progressively lowered (Colpaert et al, 1980) in animals trained to discriminate the interoceptive cues of a drug. There is also an overlap in the net effect of psychomotor stimulants and opioids on dopamine release in the striatum (Fadda et al, 2005;Murphy et al, 2001;Zocchi et al, 2003). However, this overlap occurs only at doses of morphine and cocaine that would not be expected to induce detectable levels of dopamine release as measured by in vivo microdialysis in the C57BL/6 mouse (Rouge-Pont et al, 2002), although in CD1 mice the dopamine levels are comparable following low doses (Zocchi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%